Journal Of Indonesia Economy & Bisnis = Jurnal Ekonomi & Bisnis Indonesia - Yudistira Hendra Permana (Faculty of Economic & Business Universitas Gadjah Mada, 2010)
NO. Penulis --- Judul Artikel --- Halaman 1. Yudistira Hendra Permana --- Application of Rule of Law by Jurisdiction System on Illegal Logging Case in Indonesia 2002-2008 --- 261-277 2. Devanto Shasta Pratomo --- The Effects of Changes in Minimum Wage on Employment in the Covered and Uncovered Sectors in Indonesia --- 278-292 3. Bambang Riyanto --- Strategy Implementation : The Efect of Decentralization, Participation in Budget Setting, and Managers’ Attitude on Performance --- 293-307 4. Benito Rio Avianto --- Distortion of Capacity on Inter-Regional Trade of IMT-GT : Study Cases on Four Selected Provinces in Sumatra, Indonesia --- 308-324 5. R. Maryatmo --- Hypothesis Tests on Hall Permanent Income (HPI) : The Case of Indonesia --- 325-337 6. Fransiska Soejono --- Ownership Type and Company Performance : Empirical Studies in the Indonesian Stock Exchange 2006-2008 --- 338-352 7. Hendro Subekti --- The Impact of FX (Foreign Currency Exchange) on the Bottom Line of Textile/Shoes Industries Listed in Indonesia Stock Exchange 2006-2008 --- 353-368 8. Junaidi dan Jogiyanto Hartono --- Non-Financial Factors in the Going-Concern Opinion --- 369-378